PREPARATION OF THE FUTURE TEACHER OF TECHNOLOGIES FOR PROFESSIONAL PEDAGOGICAL ACTIVITY ON THE BASIS OF INTERDISCIPLINARY INTEGRATION (Pedagogy of Higher and Secondary Education, 2022)
The article describes the current siate and the theoretical bases for training future teachers in pedagogical institutes of lechnology, its structure and content, proved the role and importance of the integrat approach in the educational process in higher education, the characteristic pedagogical conditions for effect implementation of interdisciplinary integration, developed a model of integrative training of future teachers professional and educational activities.
Keywords: interdisciplinary integration; integrative model of training; teacher training technology